Observed Hemispheric Asymmetry in Stratospheric Transport Trends From 1994 to 2018. Issue 17 (28th August 2020) - Strahan, Susan E.; Smale, Dan; Douglass, Anne R.; Blumenstock, Thomas; Hannigan, James W.; Hase, Frank; Jones, Nicholas B.; Mahieu, Emmanuel; Notholt, Justus; Oman, Luke D.; Ortega, Ivan; Palm, Mathias; et al.
Abstract: Total columns of the trace gases nitric acid (HNO3 ) and hydrogen chloride (HCl) are sensitive to variations in the lower stratospheric age of air, a quantity that describes transport time scales in the stratosphere. Analyses of HNO3 and HCl columns from the Network for the Detection of Atmospheric Composition Change panning 77°S to 79°N have detected changes in the extratropical stratospheric transport circulation from 1994 to 2018. The HNO3 and HCl analyses combined with the age of air from a simulation using the MERRA2 reanalysis show that the Southern Hemisphere lower stratosphere has become 1 month/decade younger relative to the Northern Hemisphere, largely driven by the Southern Hemisphere transport circulation. The analyses reveal multiyear anomalies with a 5‐ to 7‐year period driven by interactions between the circulation and the quasi‐biennial oscillation in tropical winds. This hitherto unrecognized variability is large relative to hemispheric transport trends and may bias ozone trend regressions. Plain Language Summary: Our analyses of the 25‐year Network for the Detection of Atmospheric Composition Change column HNO3 and HCl data records from nine stations provide observational evidence that air in the Southern Hemisphere lower stratosphere has been getting younger relative to the Northern Hemisphere at a rate of 1 month/decade since 1994. This stands in contrast to several model studies that predict that Antarctic ozone hole recovery in this century will increase the Southern Hemisphere age of air relative to the Northern Hemisphere. The analyses also reveal extratropical variability with a 5‐ to 7‐year period driven by interactions between the circulation and tropical winds. This previously unrecognized, low‐frequency variability is much larger than hemispheric transport trends and is likely to cause bias in trends calculated using data records shorter than about two decades. Understanding and quantifying changes in the transport circulation matters to our ability to model how our protective O3 layer will evolve in the future. Key Points: Trace gas data show southern stratospheric air is getting younger relative to the Northern Hemisphere, in contrast to model predictions Both extratropical hemispheres have dynamically driven 5‐ to 7‐year periodicity with large amplitude relative to the age trend Multidecadal data sets are required to quantify transport trends that are not confounded by large extratropical variability